2016
DOI: 10.3415/vcot-15-11-0192
|View full text |Cite
|
Sign up to set email alerts
|

Pullout strength of monocortical and bicortical screws in meta -physeal and diaphyseal regions of the canine humerus

Abstract: Cortical thickness and bone density measurements were obtained from multiple regions of the canine humerus using QCT. Use of short monocortical screws may contribute to failure of locking plate fixation of humeral fractures, especially when placed in the condyle. When bicortical screw placement is not possible, maximizing monocortical screw length may optimize fixation stability for distal humeral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Canine femoral diaphyseal cortical bone has been shown to have a density similar to that of the 50 PCF foam, 12 so 40 PCF foam sheets were used in addition to replicate other areas of the canine skeleton likely having a lower density than the femoral diaphysis, such as humeral diaphysis and condyle. 11 The 20 PCF cellular foam block has a density similar to canine femoral cancellous bone. 12 For the polyurethane sheets, the material was cut into 3 cm x 3 cm squares with an oscillating sagittal saw and mounted into a vice with a central marked target for the surgeon to begin the drill hole.…”
Section: Materials and Methods Synthetic Bone Model Testingmentioning
confidence: 99%
“…Canine femoral diaphyseal cortical bone has been shown to have a density similar to that of the 50 PCF foam, 12 so 40 PCF foam sheets were used in addition to replicate other areas of the canine skeleton likely having a lower density than the femoral diaphysis, such as humeral diaphysis and condyle. 11 The 20 PCF cellular foam block has a density similar to canine femoral cancellous bone. 12 For the polyurethane sheets, the material was cut into 3 cm x 3 cm squares with an oscillating sagittal saw and mounted into a vice with a central marked target for the surgeon to begin the drill hole.…”
Section: Materials and Methods Synthetic Bone Model Testingmentioning
confidence: 99%
“…A 2.4 mm 10-hole reconstruction locking plate was used and a transcondylar locking screw placed, which adds stability to this type of fracture; a transcondylar screw has been shown to have a greater pull-out strength than screws placed in other locations in the humerus in a canine study 19 and this screw placement is also helpful when there is minimal bone stock available in the distal fragment and when avoiding the supratrochlear foramen. The remaining screws were then inserted.…”
Section: Diaphyseal Fractures Of the Humerusmentioning
confidence: 99%
“…This is a reasonable alternative option to avoid complications related to bicortical screws 11 . Studies have shown that monocortical fixation using the locking plate system is as safe and secure as bicortical screw fixation, and screws with longer working lengths, even when not bicortical, were more resistant to pullout 11–13 . In this study, a fissure was determined on the cauda‐medial surface of the distal femur fragment.…”
Section: Discussionmentioning
confidence: 96%
“…11 Studies have shown that monocortical fixation using the locking plate system is as safe and secure as bicortical screw fixation, and screws with longer working lengths, even when not bicortical, were more resistant to pullout. [11][12][13] In this study, a fissure was determined on the cauda-medial surface of the distal femur fragment. Monocortical fixation was applied in order to prevent fracture.…”
Section: Discussionmentioning
confidence: 99%